Kejadian Diare pada Balita Berhubungan dengan Tingkat Pengetahuan Ibu tentang Perilaku Hidup Bersih dan Sehat (PHBS) di Rumah Tangga - Lina Munita Sari Sari; Siti Annisa Devi Trusda; Ismet Muchtar Nur (Bandung Conference Series: Medical Science, 2023)
Abstract. In Indonesia, diarrhea still become public health problem because it is the main cause of mortality among children. Java as the most populated island in Indonesia, especially East Java, has the highest cases of diarrhea in toddlers in 2017. Clean and Healthy Living Behavior (CHLB) in the household can prevent diarrhea. The purpose of this study was to analyze the relationship between the level of knowledge mothers about CHLB in the household with the incidence of diarrhea in toddlers. The method used was analytic observational with a cross sectional approach. The research subjects were 70 mothers who had toddlers who were selected using the consecutive sampling technique. Research data processing using the Chi-square test. The results showed that 55 people (79%) had good CHLB knowledge, 15 people (21%) had sufficient CHLB knowledge. Meanwhile, 19 respondents (27%) had diarrhea, and the 51 people (73%) had no diarrhea, and there was a significant relationship between the level of knowledge mothers about PHBS in the household and the incidence of diarrhea in toddlers with P-value of 0.016 (<0.05). So it can be concluded that there is a relationship between the level of knowledge of mothers about PHBS in the household and incidence of diarrhea in toddlers in Lajing Village, Arosbaya District, Bangkalan Regency. Toddlers experiencing diarrhea occur not only due to poor knowledge of CHLB, but can also be caused by factors of consuming food that is not fully cooked and poor hygiene of milk bottles. Keywords: CHLB, Diarrhea Incidence, Mother's Knowledge, Toddlers. Abstrak. Diare pada balita merupakan masalah kesehatan masyarakat Indonesia karena termasuk penyebab utama kematian anak. Pada tahun 2017, kasus diare pada balita di Jawa Timur menempati peringkat kedua tertinggi di Indonesia. Kejadian diare dapat dicegah dengan menerapkan Perilaku Hidup Bersih dan Sehat (PHBS) di rumah tangga. Tujuan penelitian ini yaitu menganalisis hubungan tingkat pengetahuan ibu tentang PHBS di rumah tangga dengan kejadian diare pada balita. Metode yang digunakan adalah observasional analitik dengan pendekatan Cross Sectional, dengan subjek berjumlah 70 orang Ibu yang memiliki balita. Pengolahan data memakai uji Chi-square. Hasil penelitian menunjukkan sebanyak 55 orang (79%) pengetahuan PHBS baik, 15 orang (21%) pengetahuan PHBS cukup. Sedangkan 19 orang (27%) responden memiki balita dengan diare, dan 51 orang (73%) memiliki balita tidak diare. Terdapat hubungan yang bermakna antara tingkat pengetahuan ibu tentang PHBS di rumah tangga dengan kejadian diare pada balita dengan (p=0,016). Dapat disimpulkan, terdapat hubungan antara tingkat pengetahuan ibu tentang PHBS di rumah tangga dengan kejadian diare pada balita di Kelurahan Lajing Kecamatan Arosbaya Kabupaten Bangkalan. Kejadian diare pada balita terjadi bukan hanya karena pengetahuan ibu tentang PHBS yang kurang baik, melainkan juga bisa disebabkan oleh faktor kebersihan makanan balita. Kata Kunci: Balita, Kejadian Diare, Pengetahuan Ibu, PHBS.